Carpal Tunnel Syndrome's Laboratory Testing: Current Practice in an Academic Center in Western Saudi Arabia - Abdulraheem M. Alshehri, (Journal of King Abdulaziz University: Medical Sciences, 2023)
There is no consensus to obtain screening blood tests after carpal tunnel syndrome electro-diagnosis, nor does medical literature provide a clear cut indication. A retrospective review of 140 consecutive adult patients diagnosed with carpal tunnel syndrome between January and December 2010, at King Abdulaziz University Hospital electrophysiology laboratory, looking at screening blood tests ordered by their various practitioners to diagnose commonly associated clinical conditions with carpal tunnel syndrome, namely: Diabetes mellitus, hypothyroidism and connective tissue diseases. Around one third of patients had screening for diabetes mellitus with one or more of the following: fasting blood glucose, random blood glucose, two hours glucose testing or glycated hemoglobin. All patients who were found to have abnormal glucose values were known diabetics. Thyroid stimulating hormone was obtained in 42 (30%) patients, only 4 patients showed abnormal values, two of them were known to have hypothyroidism on treatment, the other two patients showed a normal free thyroxine values. Erythrocyte sedimentation rate, C-reactive protein, antinuclear antibodies and rheumatoid factor were requested in a negligible number of patients and were within normal limits. Screening for clinical conditions associated with carpal tunnel syndrome in this series yielded no new cases.